PENGARUH PROFITABILITAS DAN FINANCIAL LEVERAGE TERHADAP PRAKTIK PERATAAN PENGHASILAN PADA BANK-BANK DI INDONESIA - Kustono, Alwan Sr; Kusuma Sari, Evelin Dwi (Media Riset Akuntansi, 2012)
Income  smoothing  practices  often  associated  with  management  incentives  for  putting  their interests  above  the  interests  of  company  owners.  The  aim  of  this  study  is  to  examine  the effect  of profitability  and financial leverage to the income smoothing on banks in  Indonesia. The  data  used  in  this  study  is  secondary  data  sourced  from  the  Direktori  Perbankan Indonesia,  which  is  published  by  the  Direktorat  Perizinan  Dan  Informasi  Perbankan  Bank Indonesia.  Purposive  sampling  method  is  used  for  this  study  by  specifying  certain  criteria. The results showed that the profitability give negative effect on income smoothing. Financial Leverage had  no effect  on income  smoothing. The size  of  company that is used  as  a control variable  in  this  study  did  not  give  effect  on  income  smoothing  either. Keywords:  Income  smoothing,  profitability,  financial  leverage,  firm  size